ANALISA TAMAN ATAP DALAM UPAYA MENGURANGI LIMPASAN AIR HUJAN PADA BANGUNAN PERKOTAAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
With the increasing public awareness of the human relations system with the surrounding environment, communities are beginning to shift towards better sources and methods to help improve the environment. One of the methods that began to be utilized is the application of green roof construction. There are many benefits for installing a green roof whether it is in a home or office building. The study was conducted on applicable green roof construction, the benefits of installing a green roof and a process run for a green roof installation with a construction approach applicable to urban housing buildings in Jakarta and on cost analysis on material requirements and installation. And in its efforts to reduce rainwater runoff. Green roof as one in the management of rainwater in urban areas. From the result of the research resulted the calculation on survey location percentage of runoff decrease 26%. While in the test object / mock-up there is a reduction of 95% runoff volume. It can be concluded that the use of a green roof / roof garden can reduce the runoff volume produced by rainwater, resulting in reduced surface runoff automatically reduced. This will also reduce the drainage-drainage burden of the city in accommodating water. The Roof Garden plays a role in the management of rainwater management to cope with puddles up to the danger of flooding